GAMBARAN PRAKTIK PEMBERIAN ASI OLEH IBU MENYUSUI DI DESA KRACAK KECAMATAN AJIBARANG KABUPATEN BANYUMAS TAHUN 2011 - Desi Purwasih; Reni Dwi Setyaningsih; Ikit Netra Wirakhmi (Universitas Harapan Bangsa Purwokerto, 2010)
Practice correct breastfeeding is an important factor in the management of lactation, because the correct suction will empty breasts and will stimulate the release of breastmilk, so milk can be produced according the needs of the baby. In layman's mother maybreastfeed her baby, but what about the practice of breastfeeding with appropriatefeeding technique is not widely known by the mother. Implementation of improper feedingtechniques can lead to problems during breastfeeding lasts. Some of the problems thatoften occur when breastfeeding technique is incorrect is difficult to enter the breastnipple into the baby's mouth properly, putting the problem of pain, cracked nipples.Objective to describe the practice of breastfeeding women done in the village KracakAjibarang District of Banyumas. This research method is quantitative descriptive usesprimary data taken with a questionnaire to the 93 nursing mothers in the village KracakAjibarang District of Banyumas. The results showed that most respondents knew theproper breastfeeding practices in accordance with proper feeding techniques, as many as61 respondents (65.6%). When viewed from the level of education, most respondents lastberpendididkan SMP / MTS as many as 35 respondents (37.6%), seen from the parity thatis primiparas (number of children 1) 61 respondents (65.6%), those who get resources ofhealth workers which 48 respondents (51.6%). Most of the respondents know that properbreastfeeding practices in accordance with the correct breastfeeding technique as manyas 61 respondents (65.6%) Keyword : Practice of Breasfeeding, Breastfeeding